Analisis efektivitas mesin bordir komputer fuhao menggunakan metode Overall Equipment Effectiveness (OEE) dan Six Big Losses (Studi kasus: UKM XYZ) - Nasrudin, Slamet; Irwati, Dwi; Miharja, Muhammad Najamuddin Dwi (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
UKM XYZ is a computer embroidery service business. Based on observations and interviews with the head of production, computer embroidery machines often experience problems and cause machine downtime every month which can cause losses. This study aims to analyze the effectiveness of computer embroidery machines using the Overall Equipment Effectiveness (OEE) method and identify the causes of losses using the Six Big Losses. After knowing the cause of the low effectiveness of the machine, the next step is to identify it using the Fishbone Diagram, then provide suggestions for improvement. The results showed that the calculation of OEE resulted in an average value of 76.46%, in the context of JIPM standards categorized as “MEDIUM”, the calculation of Six Big Losses the cause of the highest losses is Reduced Speed Losses with a value of 15.57% and Idling & Minor Stoppage Losses as much as 13.34%. Based on the Fishbone Diagram analysis, the proposed improvements to increase effectiveness are providing training to operators, conducting a daily checklist of machines, ensuring materials according to specifications and machine capabilities, implementing a preventive maintenance system, implementing a 5 R work culture.